NUMERICAL ANALYSIS OF FLEXURAL STRENGTH AND DUCTILITY OF RU-NC COMPOSITE CIRCULAR COLUMNS - Bai, Zhizhou; Chen, John (International Journal of Research -GRANTHAALAYAH, 2025)
To theoretically investigate the flexural strength and ductility of a novel composite column structure comprising a Reinforced Ultra-High Performance Concrete (RU) shell and a core Normal Concrete (NC), this study proposes a comprehensive full-range moment-curvature analysis framework. Based on the derived moment-curvature relationships, a comparative analysis is conducted between RU-NC composite circular columns and conventional NC circular columns. The results demonstrate that replacing the NC outer layer with a thin-walled UHPC shell leads to significant enhancements in both flexural strength and ductility performance. Key findings reveal that the flexural strength and ductility of both traditional NC and proposed composite RU-NC circular columns exhibit strong dependence on the applied compressive axial load level. Furthermore, these mechanical properties show a pronounced correlation with the compressive strength of UHPC. Specifically, both flexural strength and ductility are further influenced by the compressive strength of UHPC. As the UHPC compressive strength increases, these mechanical properties exhibit a marked improvement.